Pécs gazdasági változásai a világgazdasági válság idején (1929-1933) - Kaposi, Zoltán (Közép-Európai Közlemények, 2024)
This study examines the changes of the economy of Pécs, the largest city in Southern Transdanubia. Pécs was a heavily industrialised city with a population of sixty thousand in 1930. There was a quick economic development in the second half of the 1920s. During this time manufacturing industry and small businesses grew, coal mining increased, trade grew and the number of intellectuals multiplied due to the relocation of the Pozsony University to Pécs. However, the depression broke these trends. The manufacturing industry focusing on mass production faced with narrowing markets, leading to layoffs. The decrease in real wages led to a drop in small scale production and retail sales. Merchandising firms once having high turnovers conducting business regionally went into administration. The famous wine trading opportunities of Pécs decreased because of overproduction. In this study we point out, that even in these difficult years there were encouraging signs. The leather factory acquired many other firms. There was a concentration among financial institutions; the Pécsi Takarékpénztár (Pécs Savings Bank) gained strong positions. The city also engaged in different activities: public employment was initiated, new investments were started and soup kitchens were opened. The charity work of wealthy citizens and some companies were significant too. Tourism strengthened too through cheap train tickets, promotion of cultural programmes and construction of tourist hotels.